AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL 70% DAUN KELOR (Moringa oleifera Lam.) TERHADAP DPPH - Riskianto; Saenal Edi Kamal; Muh. Aris (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Kelor (Moringa oleifera Lam.) leaves have traditionally been known to have various efficacy of properties and based on previous research states that the content of M. oleifera leaves contain compounds that act as antioxidants. This study aims to examine the antioxidant activity of 70% ethanol extract of M. oleifera leaves. Maceration of M. oleifera leaves using 70% ethanol solvent, the extract obtained was carried out by phytochemical screening, then testing the activity of 1,1-Diphenyl-2-Picryl Hydrazyl (DPPH). The yield of extract obtained was 7,36%. The phytochemical screening on 70% ethanol extract of M. oleifera leaves contained alkaloids, flavonoids, phenols, and tannins. The antioxidant activity test showed that the IC50 value of 70% ethanol extract of M. oleifera leaves was 50,595 μg/mL, and the IC50 quercetin value was 0,538 μg/mL. Antioxidant Activity Index (AAI) of 70% ethanol extract of M. oleifera leaves was (0,988) and AAI of quercetin was 92,936. Based on the results, it is obvious that the 70% ethanol extract of M. oleifera leaves has moderate antioxidant activity and a source of natural antioxidants.